Komparasi Pendapatan Usaha Tani Padi Karang Dukuh Di Dua Tipe Pasang Surut Kecamatan Mandastana - Arif, Arif Dwi Adrianto; Ari Jumadi Kirnadi; Inda Ilma Ifada (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2022)
The Tabing Rimbah Village and Puntik Dalam Village are villages located in Mandastana District. Tabing Rimbah Village with typology B has 482 m2 of land, while Puntik Dalam Village has 91 m2 of land with typology C. From land types B and C tidal in Mandastana District there are different types of land, these differences will affect the production of rice produced which results in the income received by farmers. This study aims to determine the comparative income of rice farming in Karang Hamlet in two different types of tides in Mandastana District. The research was conducted in November 2021. The population was 165 type B rice farmers and 153 type C rice farmers with a sample of 15 type B farmers and 15 type C farmers using a purposive sampling technique. Data analysis used descriptive analysis, cost analysis and income comparison with the T test. The results showed that the income of type B tidal farmers obtained a total explicit cost of Rp. 629,236,127 and type C Rp.610,820,680 while the implicit cost for type B Rp.213,037,500 and type C Rp.203,267,750. With a total cost of Rp.842,273,627 for type B and Rp.814,088,430 for type C. There is a significant average difference in grain and rice income for farmers in type B and C tidal land in Mandastana District.